The Role of Tax Knowledge, Tax Understanding, Tax Digitalization, and Motivation in Enhancing MSME Taxpayer Compliance - Paska Lumban Gaol; Lia Dama Yanti (Komunitas Dosen Indonesia, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in Indonesia's economy by promoting economic growth and creating employment opportunities. Despite their substantial contribution, tax compliance among MSME taxpayers remains a persistent challenge. This study investigates the effects of tax knowledge, tax understanding, tax digitalization, and motivation on taxpayer compliance among MSME owners in Legok Village. A quantitative research design was employed using primary data collected through an online questionnaire distributed via Google Forms. The study involved all 85 active MSMEs in Legok Village using a census sampling approach. The collected data were analyzed using SPSS version 27 through validity, reliability, normality, multicollinearity, multiple linear regression, coefficient of determination, t-test, and F-test analyses. The findings reveal that tax knowledge has no significant effect on taxpayer compliance (t = 1.140, p = 0.258), while tax understanding has a positive and significant effect (t = 6.421, p < 0.001). Tax digitalization exhibits a significant negative effect on taxpayer compliance (t = -6.629, p < 0.001), whereas motivation does not significantly influence taxpayer compliance (t = –0.280, p = 0.780). Furthermore, the simultaneous test demonstrates that tax knowledge, tax understanding, tax digitalization, and motivation collectively have a significant effect on MSME taxpayer compliance (F = 22.012, p < 0.001). These findings suggest that improving taxpayer compliance requires not only adequate tax knowledge but, more importantly, a deeper understanding of tax regulations and greater readiness to adopt digital taxation systems.